1972
DOI: 10.1119/1.1986818
|View full text |Cite
|
Sign up to set email alerts
|

Keller vs Lecture Method in General Physics Instruction

Abstract: A description of the use of the Keller method of instruction in a general physics class of 100 students is presented. This teaching technique is critically evaluated by comparing the performance of the students in the program with that of 100 students in a concurrent control group run by the traditional lecture method. It is found that performances are not significantly different and the cost of running the program is not excessive. Furthermore, student reaction to the program is found to be quite favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…These investigators report that 87% of the students in a course in behavior analysis felt that they learned more from PSI than they would have from a lecture course; 13% felt that the amount learned was equal; none felt that they had learned less. Similar results are reported by Simmons (1972), Dealy, Fuller, andWeber (1973), Gallup (1970), Philippas andSommerfeldt (1972), Billings (1972), and Moore, Mahan, and Ritts (1969).…”
Section: Other Indicators Of Content Learningsupporting
confidence: 84%
See 1 more Smart Citation
“…These investigators report that 87% of the students in a course in behavior analysis felt that they learned more from PSI than they would have from a lecture course; 13% felt that the amount learned was equal; none felt that they had learned less. Similar results are reported by Simmons (1972), Dealy, Fuller, andWeber (1973), Gallup (1970), Philippas andSommerfeldt (1972), Billings (1972), and Moore, Mahan, and Ritts (1969).…”
Section: Other Indicators Of Content Learningsupporting
confidence: 84%
“…No one felt that the amount of time required in the PSI section was less. Reports of other investigators are similar (Billings, 1972;Gallup, 1970;Gentile, 1971;Hapkiewicz, 1972;Hoberock et al, 1972;Nelson & Scott, 1972;Philippas & Sommerfeldt, 1972;Simmons, 1972).…”
Section: Other Indicators Of Content Learningmentioning
confidence: 55%
“…There is considerable evidence that students taught by the PSI approach perform better on examinations covering course content than students taught by a lecture approach (2 , 8, 9). Studies have also shown that student attitudes are more favorable toward PSI than toward lecture·type courses (6,11,16).…”
Section: Instructor-pacingmentioning
confidence: 94%
“…3 Experimental designs classified according to Campbell and Stanley (1963). Born et al (1972) ..... Born & Whelan (1973) .......... Breland & Smith (1975) Kulik, & Milholland (1974) .. McMichael & Corey (1969) ...... 0 0 0 Morris & Kimbrell (1972) ........ 0 0 0 Philippas & Sommerfeldt (1972) .. Sheppard & McDermot (1970) ... (> » Scores of mastery group statistically greater than scores of nonmastery group (p < .05).…”
Section: The Type 2 Researchmentioning
confidence: 99%